NEW MOVEMENT LOCAL WISDOMNOMIC: STUDY OF MAWAH AS A MODEL OF COMMUNITY ECONOMIC EMPOWERMENT - Iskandar; Juliana Putri; Razali (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2023)
This research discusses the topic of Acehnese cultural issues, namely mawah which is a concept of local wisdom and an important role in the life of the Acehnese. The two main topics of this research are mawah dialectics in the socio-economy of the Acehnese, and the mawah model as empowering the modern economy of society. The method used in this research is qualitative through a philosophical normative approach. Data collection was carried out through interviews, observation, documentation, and FGD (Focus Group Discussion). The results of this study indicate that the Mawah dialect in the socio-economy of the people of Aceh occurs in several stages. Mawah first stage concentrated on breeding. is termed as “Mawah Aneuk Nang” In mawah which is divided between owners and breeders is about 50:50 distribution or depending on how the mawah was originally carried out. There are several mawah principles in empowering the Acehnese economy, namely the principles of al’adalah, at-t’awun and musawwamah. Mawah can be a model of massive modern agrarian economic empowerment if it is managed properly and involves professional parties. Some of the things that must be done are to establish Mawah Boards (BW) which are backed up by the district and village governments, then create networks and relationships as a gateway for mawah online. At this final stage, mawah becomes a start-up business.